Peningkatan Prestasi Belajar Bahasa Inggris pada Pokok Bahasan Narrative Reading melalui Media Gambar di Madrasah Aliyah Negeri 4 Sleman - Hanti Watmi Rejeki (Jurnal Pendidikan Madrasah, 2022)
This study discusses the use of image media to increase students' understanding and activeness in learning English on the subject of narative reading. This research was conducted on class XI social studies 3 MAN 4 Sleman students with a total of 17 students. The method used in this study is a class action research method. Each cycle goes through the stages of planning, execution, observation, and reflection. From the results of the first cycle research, students who obtained a score of > 70 were 50.58% with sufficient categories. The test results in cycle II of students who obtained a score of > 70 were 100% with an active category. The use of image media successfully optimizes students' ability to understand narrative text and increases the effectiveness of student learning.